Effects of emamectin benzoate on pharmacokinetic profiles, bioavailability, and serum biochemical indices in crucian carp (Carassius carassius) following oral administration with multiple dosage levels - Sun, RuYu; Liu, YongTao; Ai, XiaoHui; Du, XiangXuan; Zhang, XiaoYi (Frontiers in Veterinary Science, 2023)
The aim of this investigation was to explore the effect of three different dose levels of emamectin benzoate (EMB) (50, 200, and 500 μg/kg bw) on pharmacokinetic characterizations, tissue distribution patterns, absolute bioavailability, and serum biochemical indices in crucian carp following oral administration at 22 ± 2°C, respectively. We further calculated the relevant parameters by detecting the concentration of EMB in the crucian carp by the ultra-HPLC detection method. The results showed that Cmax, AUC, and T1/2z after oral administration showed a dose-dependent increase in plasma. Secondly, EMB has a long mean flow time (MRT) (51.88, 67.04, and 78.00 h, respectively). In conclusion, the elimination of the drug is slow, and the higher dose used, the slower elimination is. The distribution in various tissues of crucian carp was analyzed. The order of EMB levels in tissues of crucian carp was liver > gill > kidney > muscle plus skin > plasma. As for pharmacokinetic parameters in tissues, Cmax, AUC, and T1/2z in tissues had a similar pattern as that in plasma. The absolute oral bioavailability of EMB (F%) in crucian carp was calculated to be approximately 52.70%. The serum biochemical indices including ALT and AST in experimental groups exhibited significant differences (P < 0.05) compared with the control group while ALB, ALP, TP, T-CHO, BUN, GRE, and GLU were not significantly different to the control group (P > 0.05). Briefly, EMB has the characteristic of quick absorption and slow elimination in crucian carp with a high bioavailability by PO route in crucian carp.